(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The patterns of seasonal and daily activities of two parthenogenetic species of lizards (Darevskia armeniaca, D. unisexualis) sharing the same territories in the zone of hybridization in central region of Armenia demonstrate ecologically similar potential niches.